Clto open heart as operative treatment of foreign body In the left ventricle removal - M. Rosadi Seswandhana, M. Rosadi Seswandhana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Foreign body in the left ventricle is rare and it is associated most commonly with significant trauma. The diagnosis of a foreign body in the left ventricle can be difficult. One must distinguish between foreign matter in the cardiac chamber or free-floating in the mediastinum. Our case was male, 38 years old. He presented not only with typical complaints of chest pain and dyspnea, but also with the complaint of a